A QUICK-LOOK SIMULATION STUDY ON THE FULL FIELD MODEL OF THE JATIBARANG VOLCANICS - Thawer. R; Syahrial. E (Scientific Contributions Oil and Gas, 1993)
A full field simulation study was carried out on the Jatibarang Formation volcanics reservoir in the Jatibarang field. A model developed during a study carried out by LEMIGAS in 1988, up-dated to incorporate current analyses on logs and well tests, was used.